New Approach of Islamic Teaching for Transgender: A Case Study in Indonesia - Adinda Arifiah; Muhammad Nur Ichsan; Ayu Lestari (Anjasmoro: Islamic Interdisciplinary Journal, 2025)
Transgender people in Indonesia cause much debate and even encourage the emergence of discriminatory behavior in society. This is because it is contrary socially, culturally, and religiously. The emergence of the first Transgender Islamic Boarding School was established in Yogyakarta as a socio-religious reality from the perspective of marginalized people which is very interesting to study. This research focuses on Islamic teachings for transgender at the Al-Fatah Islamic Boarding School Yogyakarta and how the approach is carried out in the learning process. This research uses case study methods with data collection techniques in the form of in-depth interviews to explore informant information consisting of 3 types of informants: the teaching staff, the students, and the management. The results showed that the Islamic teachings are oriented to 3 aspects: 1) Aspects of Worship, 2) Discussion Forum to strengthen knowledge and understanding of Islam, and 3) Entrepreneurial Competence Development. Exemplary methods, habituation, and conversation methods generally carry out the learning process. This learning method is carried out with a good, polite, gentle, and easy-to-understand word approach.